The two faces of giant cell tumor of bone. (1st October 2020) - Scotto di Carlo, Federica; Whyte, Michael P.; Gianfrancesco, Fernando
Abstract: Giant cell tumor (GCT) is a bone-destructive benign neoplasm characterized by distinctive multinucleated osteoclast-like giant cells with osteolytic properties distributed among neoplastic stromal cells. GCT is locally aggressive with progressive invasion of adjacent tissues and occasionally displays malignant characteristics including lung metastasis. GCT is characterized genetically by highly recurrent somatic mutations at the G34 position of the H3F3A gene, encoding the histone variant H3.3, in stromal cells. This leads to deregulated gene expression and increased proliferation of mutation-bearing cells. However, when GCT complicates Paget disease of bone (GCT/PDB) it behaves differently, showing a more malignant phenotype with 5-year survival less than 50%. GCT/PDB is caused by a germline mutation in the ZNF687 gene, which encodes a transcription factor involved in the repression of genes surrounding DNA double-strand breaks to promote repair by homologous recombination. Identification of these driver mutations led to novel diagnostic tools for distinguishing between these two tumors and other osteoclast-rich neoplasms. Herein, we review the clinical, histological, and molecular features of GCT in different contexts focusing also on pharmacological treatments.